Dealer-Manufacturer Relationship in the Automobile Industry: Reply - Koo, Anthony Y. C. (Quarterly Journal of Economics, 1960)
Journal Article Dealer-Manufacturer Relationship in the Automobile Industry: Reply Get access Anthony Y. C. Koo Anthony Y. C. Koo Michigan State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 74, Issue 2, May 1960, Pages 333–337, https://doi.org/10.2307/1884260 Published: 01 May 1960